Synthesis of MgNb2O6 by coprecipitation - Navale, S. C.; Gaikwad, A. B.; Ravi, V. (Materials Research Bulletin, 2006)
A simple coprecipitation technique was used successfully to synthesize fine powders of MgNb2O6 (MN) phase. An aqueous mixture of ammonium carbonate and ammonium hydroxide was used to precipitate Mg2+ and Nb5+ cations as carbonate and hydroxide respectively under basic conditions. This precipitate on heating at 750 degrees C produced MN powders. For comparison MN powders were prepared by the traditional solid state method. The phase content and the lattice parameters were studied by powder X-ray diffraction (XRD). Particle size and morphology of the particles were studied by scanning electron microscopy (SEM). (C) 2006 Elsevier Ltd. All rights reserved.
Keywords: Ceramics; Chemical synthesis; Electron microscopy; electronic materials; X-ray diffraction